UNIVERSITY ELEARNING ENVIRONMENT MODEL - Irina K. Voytovich (Высшее образование в России)
Abstract. The model of e-learning environment built on the basis of cyclic principles, consistency and innovation is being discussed. Its main components are the leadership, normative framework, educational, informational, technological, and physical space components. Each component in itself comprises a complex subsystem with a specific content, participants, objectives, and actions. Non-directional nature of the sequence diagram that represents the model reflects the possibility of formation of e-learning at university in any workflow. The presented e-learning environment model is universal. On the one hand, it gives the opportunity to create an educational institution e-learning environment for hybrid, distant or mobile types of e-learning. On the other hand, the model meets the needs of any educational institution and can be viewed upon as a basis for the implementation strategy of e-learning technologies.